1983
DOI: 10.1021/ma00244a012
|View full text |Cite
|
Sign up to set email alerts
|

The model parameters of helical wormlike chains

Abstract: 1613gether with the values of the parameters EkT/Vo, K and { that characterize networks A and B, respectively (see text), one may evaluate x by solution of eq A-5. Results are given in Table 11.Equation A-10 in conjunction with A-7 may be solved iteratively for u i , given the network parameters, the value of x, and the extension ratio a, relative to the system swollen to equilibrium under isotropic conditions. The reduced force that would obtain if further swelling did not occur as a result of the elongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 33 publications
1
30
2
Order By: Relevance
“…Yamakawa and coworkers 26 found that the Monte Carlo data of Jordan et al 8 for the persistence vector and <R 2 ) (without excluded volume) are accurately reproduced by HW theoretical curves (for an appropriately chosen set of parameters) over the entire possible range of x ( 2) when the HW chain contour is taken along the helical sequence. The chain contour so chosen corresponds to a small length scale of one glucose residue.…”
Section: Z = (3/2n) 312 B(al) 112mentioning
confidence: 96%
See 1 more Smart Citation
“…Yamakawa and coworkers 26 found that the Monte Carlo data of Jordan et al 8 for the persistence vector and <R 2 ) (without excluded volume) are accurately reproduced by HW theoretical curves (for an appropriately chosen set of parameters) over the entire possible range of x ( 2) when the HW chain contour is taken along the helical sequence. The chain contour so chosen corresponds to a small length scale of one glucose residue.…”
Section: Z = (3/2n) 312 B(al) 112mentioning
confidence: 96%
“…The chain contour so chosen corresponds to a small length scale of one glucose residue. On the other hand, if the contour is taken along the helix axis, i.e., if a large length scale of a few glucose units (relevant to analysis of data for steady-state transport coefficients) 26 is adopted, the HW thoretical curve for <R 2 ) deviates downward from the Monte Carlo data at x smaller than 10 (see Figure 9 of ref 26). The analysis of [11] made by Nakanishi et al indeed refers to such a large length scale of two to four glucose residues.…”
Section: Z = (3/2n) 312 B(al) 112mentioning
confidence: 99%
“…However, it can be said that these three polymers of the adjusted racemo fractions essentially have the helical nature. The values of Ko and To for these polymers indicate that these three polymers belong to the domain I defined in ref 27.…”
Section: Determination Of the Static Chain Stiffnessmentioning
confidence: 66%
“…In addition, the tendency to take the tt conformation leads to the helical nature for the syndiotactic chains. The values of Ko and To show that the syndiotactic PMMA and syndiotactic PEMA belong to the domain I defined in ref 27, which corresponds to a region for the typical HW chain. As for the racemo diad, we can see also qualitatively from the partition functions that the tendency of taking the tt conformation is slightly stronger for MMA than for EMA, i.e., Ztt,r/zgt,r(MMA) > Ztt,r/zgt,r(EMA), The relatively high probability of taking the tt conformation for the racemo diad of MMA is due to the instability of the gt state compared to the tt state, However, the reason for this is not clear at present.…”
Section: Determination Of the Static Chain Stiffnessmentioning
confidence: 78%
See 1 more Smart Citation